Medical Wikipetia: A New Electronic Tool in Education - Pontes Gomes de Matos, Paulo Marcelo; Cruz de Almeida, Flora; Perdigão Cordeiro, Anna Beatriz; Lima Vale, Mariana (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2013)
WikiPETia Médica is an initiative from the group PET Medicina that aims to assist medical teaching through the publication of online summaries. The project consists in the development of texts, based on revisions of recognized medical bibliography, which are meant to be used for the study of medical subjects. Those texts are published in an online platform and organized according to the curriculum of the Federal University of Ceará School of Medicine. Monthly each of the 12 students of the group is responsible for updating the platform with a new text. This way, until the end of each month the website will contain 12 new short and reliable texts of many different subjects from the medical universe. Currently WikiPETia Médica has approximately 250 texts. The statistics shows a total accesses number of 754.147 since its creation in 2009.